Phonological Errors of Juz Amma in 1st grade of RTQ Al Ghozali Malang - Diandra Ariesta Lily Effendi Al Azhim (Universitas Negeri Malang, 2023)
Phonological errors are language errors in pronunciation that are produced by human speech tools, that causing differences meaning. So the need for accuracy in pronouncing a letter or word in accordance with the appropriate articulation. This article tries to describes the forms of the phonological errors of juz amma, and also the factors that influence the phonological errors of juz amma and the solutions to minimize the phonological errors of juz amma. This research is a descriptive qualitative research. The data collection techniques used the method of observation, interviews, study literature and documentation. The data analysis technique of this research are data collection, sorting and selecting data, presenting data and taking conclusions. The data source of this research is based on the results of observations on the students of RTQ Al-Ghozali Malang. The result of this research is phonological errors of juz amma in 1st grade, both in terms of pronouncation and the long and short verses. The causative factors are inappropriate language acquisition, lack of interest in learning, habituation factors and social support factors. So that the solution is to emphasize the teacher's pronunciation in reciting juz amma correctly, motivating children to learn, continuous good habituation, and the importance of support system.